Muhammad Abduh’s Thought on Islamic Education Reform and Its Contemporary Implications in Indonesia - Akbar, Rahmadani; Alkhadafi, Rahmad; Muzammil, Shofiyullah (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2025)
This study aims to analyze Muhammad Abduh's thoughts on Islamic educational reform and describe their relevance to the dynamics of contemporary Islamic education in Indonesia. Using a literature review method with descriptive-critical analysis of Abduh's primary works and secondary literature, this study identified four main ideas of reform: Abduh's rejection of blind imitation and his encouragement to develop a culture of critical thinking; criticism of tendentious books that paved the way for strengthening critical literacy and developing more objective teaching materials; reform of educational institutions that emphasized the integration of religious and modern sciences; and revitalization of the Islamic intellectual heritage (turats) through a contextual and interdisciplinary approach to reading. These findings show that Abduh's thinking can provide philosophical and practical direction for the development of madrasah and pesantren curricula, the improvement of teacher competence, and the modernization of learning methods that are more dialogical, rational, and adaptive to the challenges of the 21st century. Thus, this study contributes to explaining how Abduh's reformist ideas can be implemented to strengthen the quality and relevance of Islamic education in Indonesia.